Activation of defense enzymes in arecanut (Areca catechu L.) seedlings upon inoculation with biocontrol agents - Kannan, C.; Jose, C.T. (Journal of Plantation Crops, 2009)
The effect of soil application of three biocontrol agents viz., Pseudomonas fluorescens, Bacillus subtilis and Trichoderma viride on arecanut seedlings were studied with respect to the induction, dynamics and persistence of activity of the defense enzymes viz., peroxidase, poly phenol oxidase, phenyl alanine ammonia lyase, catalase and chitinase. Results showed that the biocontrol agents differed in their ability to activate different enzymes and sustain their persistence in the seedlings.